Peptidoglycan Muropeptides: Release, Perception, and Functions as Signaling Molecules - Irazoki, Oihane; Hernandez, Sara B.; Cava, Felipe (Frontiers in Microbiology, 2019)
Peptidoglycan (PG) is an essential molecule for the survival of bacteria and thus its biosynthesis and remodelling have always been in the spotlight when it comes to the development of antibiotics. The peptidoglycan polymer provides a protective function in bacteria, but at the same time is continuously subjected to editing activities that in some cases lead to the release of peptidoglycan fragments (i.e., muropeptides) to the environment. Several soluble muropeptides have been reported to work as signalling molecules. In this review, we summarize the mechanisms involved in muropeptide release (PG breakdown and PG recycling) and describe the known PG-receptor proteins responsible for PG sensing. Furthermore, we overview the role of muropeptides as signalling molecules, focusing on the microbial responses and their functions in the host beyond their immunostimulatory activity.